Advances in immunology. - Alt, Frederick W.; Murphy, Kenneth (Kenneth M.) (Advances in immunology, 2024)
Advances in Immunology, Volume 163, the latest release in a long-established and highly respected publication, presents current developments and comprehensive reviews in immunology. Sample chapters include The role of autophagy in RIP1 mediated cell death and intestinal inflammation, IL-17 family cytokines in inflammatory or autoimmune kin diseases, and more.